A MULTIMODAL DISCOURSE OF PROMOTIONAL VIDEO WONDERFUL INDONESIA - Muhammad Ansori; Lita Liviani Taopan (UIN Alauddin Makassar, 2019)
This study aimed at exploring the ideational and representational meaning of a promotional video Wonderful Indonesia. By applying the Systemic Functional Linguistics and Visual Grammar framework, this study views how the verbal and visual modes construe the meaning in the video. It is concluded that verbal mode contributes to build ideational meaning that intended to promote tourism as well as to persuade the tourists to visit Indonesia. Besides, the visual modes successfully depict both conceptual and narrative representation that are the hospitality of local people, the diversity of culture, the beauty of nature, and the modernity of Indonesia. At the end of the discussion, this study shows how to implement the dynamic modes in the context of English language teaching that will be beneficial for teaching ESP and vocational school. Keywords: Multimodal discourse analysis, ideational meaning, representational meaning, promotional videoABSTRAK Penelitian ini bertujuan untuk mengeksplorasi makna ideasional dan representasional dari video promosi Wonderful Indonesia. Dengan menerapkan Linguistik Fungsional Sistem dan bingkai Tata Bahasa Visual, penelitian ini melihat bagaimana mode verbal dan visual menafsirkan makna dalam video. Dapat disimpulkan bahwa mode verbal berkontribusi untuk membangun makna ideasional yang dimaksudkan untuk mempromosikan pariwisata serta membujuk para wisatawan untuk mengunjungi Indonesia. Selain itu, mode visual berhasil menggambarkan representasi konseptual dan naratif yang ramah masyarakat setempat, keanekaragaman budaya, keindahan alam, dan modernitas Indonesia. Pada akhir diskusi, penelitian ini menunjukkan bagaimana menerapkan mode dinamis dalam konteks pengajaran bahasa Inggris yang akan bermanfaat untuk pengajaran ESP dan sekolah kejuruan. Kata kunci: Analisis wacana multimodal, makna ideasional, makna representasional, video promosi